2019
DOI: 10.24191/myse.v6i2.8684
|View full text |Cite
|
Sign up to set email alerts
|

A REVIEW OF SEATING ARRANGEMENTS TOWARDS THE 21st CENTURY CLASSROOM APPROACH IN SCHOOLS

Abstract: This article articulates a framework suitable to use when making a decision about student seating arrangement in the classroom at school level as a research aim. The decision makers should establish what are the potential types of seating arrangement? Then evaluate them in terms of its contribution, significance, and impact to the student learning development. The problem of a seating arrangement is usually related to the seating student position selection that is usually decided by teachers or students that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
11
1
Order By: Relevance
“…The teaching profession must continually develop creative new ways of working with others (Florian and Sprat, 2013 [175]).…”
Section: Developing Inclusive Pedagogiesmentioning
confidence: 99%
“…The teaching profession must continually develop creative new ways of working with others (Florian and Sprat, 2013 [175]).…”
Section: Developing Inclusive Pedagogiesmentioning
confidence: 99%
“…Alternatively, the student-centered approach allows students to work together and usually corresponds to the aggregation of desks (i.e., clusters). Both traditional seating in single desks and teacher-centered approaches are the globally dominant approaches (Blackmore, Bateman, Loughlin, O’Mara, & Loughlin, 2011 ), despite the fact that, in recent years, arrangement in clusters is becoming more frequent and preferred by teachers (Gremmen, van den Berg, Segers, & Cillessen, 2016 ), providing a good basis for cooperative learning and other student-centered approaches (Norazman, Ismail, Ja’afar, Khoiry, & Ani, 2019 ).…”
Section: The Role Of Seating Arrangementmentioning
confidence: 99%
“…This result is in line with previous studies that showed better functioning in creative tasks when working and interacting in groups (Milliken et al, 2003;Paulus & Yang, 2000), although in this case, children were required to solve individual tasks in a clustered disposition. However, cluster arrangement is related to cooperative learning and other student-centered approaches in the school daily life (Norazman et al, 2019), so less alone students could symbolically perceive the situation as a "group work", benefiting from Fig. 4 Moderation graph describing the effect of seating arrangement on the theory of mind (ordinate), based on children's loneliness as rated by peers (abscissa); children with a loneliness score higher than 0.71 were significantly affected by the manipulation.…”
Section: Moderating Role Of Lonelinessmentioning
confidence: 99%
“…Alternatively, the studentcentered approach allows students to work together and usually corresponds to the aggregation of desks (i.e., clusters). Both traditional seating in rows and columns and teacher-centered approaches are the globally dominant approaches (Blackmore, Bateman, Loughlin, O'Mara and Aranda 2011), despite the fact that, in recent years, arrangement in clusters is becoming more frequent and preferred by teachers (Gremmen, van den Berg, Segers and Cillessen 2016), providing a good basis for cooperative learning and other student-centered approaches (Norazman, Ismail, Ja'afar, Khoiry and Ani 2019).…”
Section: The Role Of Seating Arrangementmentioning
confidence: 99%
“…This result is in line with previous studies that showed better functioning in creative tasks when working and interacting in groups (Milliken et al 2003;Paulus and Yang 2000), although in this case, children were required to solve individual tasks in a clustered disposition. However, cluster arrangement is related to cooperative learning and other student-centered approaches in the school daily life (Norazman et al, 2019), so less alone students could symbolically perceive the situation as a "group work", bene ting from its positive consequences on a creative task. This result suggests that the mere physical proximity can lead to the bene ts that group work provides for creative thinking.…”
Section: Moderating Role Of Lonelinessmentioning
confidence: 99%